1986
DOI: 10.1172/jci112468
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lipoteichoic acid sensitizes host cells for destruction by autologous complement.

Abstract: Lipoteichoic acids (LTA) released by gram-positive bacteria can spontaneously bind to mammalian cell surfaces. In the present study, erythrocytes (E) sensitized with pneumococcal LTA (LTA-E) were used as a model system to determine if LTA could render host cells susceptible to damage by autologous complement.Complement (C)-mediated lysis of LTA-E from normal rats and normal humans occurred when these cells were incubated in their respective autologous sera in vitro. In addition, when LTA-E from a C2-deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…These findings suggest that although the Fc portion of the immunoglobulin might be unengaged, complement might not be activated under the conditions of our experiments. On the other hand, the findings that LTAanti-LTA complexes not bound to cells readily activate complement (26,27) and that complement activation resulted in the death of a variety of LTA-sensitized target cells (fibroblasts, tumor cells, and RBCs) (19,22,23) indicate that further studies to elucidate this controversial finding should be performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that although the Fc portion of the immunoglobulin might be unengaged, complement might not be activated under the conditions of our experiments. On the other hand, the findings that LTAanti-LTA complexes not bound to cells readily activate complement (26,27) and that complement activation resulted in the death of a variety of LTA-sensitized target cells (fibroblasts, tumor cells, and RBCs) (19,22,23) indicate that further studies to elucidate this controversial finding should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Since LTA-anti-LTA complexes activate complement via the classical and alternative pathways (26,77) and also since distinct cytopathic changes were induced in LTA-sensitized target cells which had been treated with complement-sufficient anti-LTA sera (19,22,23), it was also of interest to examine the possibility that complement activation might also enhance superoxide generation. In preliminary experiments performed in collaboration with Dr. G. Till, it was found that the addition of either human or guinea pig serum containing 10-20 CHso units of complement to LTA-sensitized PMNs in the presence of anti-LTA globulin did not result in a significant enhancement of superoxide generation.…”
Section: Effect Of Bystander Pmns On O~ Generation Induced By Lta-antmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, TAs function as inducers of proinflammatory mediators, immunogens, complement activators, adhesins, and mitogens (158,180,232,471). Our goal in this review is to summarize the host responses where the D-alanyl esters of TAs are implicated.…”
Section: D-alanyl Esters and Pathogenicitymentioning
confidence: 99%
“…Furthermore, other serumfactors, e.g. albumin [23] and complement [24] have been shown to either reduce binding ofLTAs to eurkaryotic cells orto induce lysis ofcells sensitized with LTAs. To avoid the effect of serum factors we used a serum-free system for the induction of cytokines and proliferation.…”
Section: Cytokine Production Ofmopmentioning
confidence: 99%